2020
DOI: 10.3390/ijerph17072476
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Red Arch-Support Insoles on Subjective Comfort and Movement Biomechanics in Various Landing Heights

Abstract: Red is perceived as a “winning color”, which may influence actual and perceived performances in sports, but little effort has been done to assess the added value on colored foot insoles in basketball movements. This study examined if colored foot insole would influence perceived comfort and lower extremity biomechanics during drop landing. Nineteen male basketball players performed drop landing trials with different insoles (red arch-support, white arch-support, and white-flat) and landing heights (0.45 and 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 56 publications
0
17
1
Order By: Relevance
“…Clinghan et al [ 35 ] measured plantar pressures, comfort scores and perceived cost of shoes at three price ranges, but found no significant associations, suggesting that comfort is highly subjective and based on individual preferences. Finally, in basketball players, Wang et al [ 100 ] evaluated comfort perceptions when performing drop landings while wearing insoles that differed according to colour and contour, and found that red insoles were perceived to be more comfortable than white insoles with the same contour.…”
Section: Resultsmentioning
confidence: 99%
“…Clinghan et al [ 35 ] measured plantar pressures, comfort scores and perceived cost of shoes at three price ranges, but found no significant associations, suggesting that comfort is highly subjective and based on individual preferences. Finally, in basketball players, Wang et al [ 100 ] evaluated comfort perceptions when performing drop landings while wearing insoles that differed according to colour and contour, and found that red insoles were perceived to be more comfortable than white insoles with the same contour.…”
Section: Resultsmentioning
confidence: 99%
“…Research suggests that the colour red may increase the strength and velocity of motor responses 10,11 . When employed within foot orthoses design, red has been associated with increased levels of perceived comfort and to be linked with significant differences in some kinetic measures at the ankle in noninjured athletes 13 . This suggests that while red coloured foot orthoses might be better avoided in the injured athlete due to the negative associations with pain (as discussed earlier), perhaps red with its associated stimulant effect 8 should be the colour of choice when foot orthoses are being provided to uninjured athletes in an attempt to improve their athletic performances.…”
Section: Discussionmentioning
confidence: 99%
“…Little attention has been given to foot orthoses colour within the scientific literature, indeed only one such study appears to have been published. Wang et al compared three different insoles in a study of perceived comfort and landing biomechanics in healthy basketball players 13 . Two of the insoles were identical in material and their surface geometry's which included an "arch support", they differed only in the colour of the top-cover; one being white and the other being red.…”
Section: Colour and Foot Orthoses Researchmentioning
confidence: 99%
“…Firstly, our participants were barefoot during trials, which may not represent the real condition of sporting activities. Bare feet are preferable because wearing shoes during trials may influence the athletes' landing strategies due to the shoes' shock absorption effect [2,32]. Secondly, although we ensured that the participants maintained their foot position during WBLT, the foot posture (i.e., pronation and supination) was not quantified.…”
Section: Discussionmentioning
confidence: 99%